Consumo, digestibilidade dos nutrientes e comportamento ingestivo de ovinos com dietas à base de feno de juazeiro (Zizyphus joazeiro) - Costa, Marcus Roberto Góes Ferreira (2008)
The intake, the apparent digestibility of nutrients and ingestive behavior of sixteen sheep of Morada Nova race with average weight of 26.75 kg, divided into individual metabolic cages, receiving diets containing crescent levels of juazeiro hay (0, 33, 67 and 100%) were evaluated. A casualized block experimental design with four treatment and four replications was used. Dry matter, organic matter, crude protein, ether extract, neutral detergent fiber,acid detergent fiber, total carbohydrates, carbohydrates fiber and non-fiber carbohydrates intakes were not influenced by addiction of juazeiro hay of the experimental diets, with average value in the 1042.78 and 595 g/day the dry mater and neutral detergent fiber, respectively. Observed a reduction linear for dry matter, organic matter, neutral detergent fiber and carbohydrates fiber digestibility. For acid detergent fiber digestibility observed a reduction quadratic. The crude protein, ether extract, total carbohydrates, carbohydrates fiber digestibility did not present significant variation. The nitrogen balance was not influencing, present positive for treatments. The inclusion of juazeiro hay did not influencing the intake of nutrients, but it reduces the digestibility coefficient in some diet components. The inclusion of hay juazeiro did not influence the ingestive behavior of animals (P> 0.05). The juazeiro hay with convection grass hay is a feeding strategy for northwest semi-arid